2023
DOI: 10.3390/molecules28020481
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Docking Study, and Antiproliferative Evaluation of Novel Schiff Base–Benzimidazole Hybrids with VEGFR-2 Inhibitory Activity

Abstract: A new series of Schiff–benzimidazole hybrids 3a–o has been designed and synthesized. The structure of the target compounds was proved by different spectroscopic and elemental analysis tools. The target compounds were evaluated for their in vitro cytotoxic activity against 60 cancer cell lines according to NCI single- and five-dose protocols. Consequently, four compounds were further examined against the most sensitive lung cancer A549 and NCI-H460 cell lines. Compounds 3e and 3g were the most active, achieving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Scheme 1 depicts the synthesis method for compounds 4a – j , 5 , and 6 . Condensation of 3,4-aminobenzoic acid with p-chlorobenzaldehyde in the presence of sodium metabisulphite and DMF resulted in the synthesis of benzimidazole-5-carboxylic acid ( 1 ) in a good yield [ 34 , 35 ]. Compound 1 ’s infrared spectra showed that C=O was present at 1662 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 1 depicts the synthesis method for compounds 4a – j , 5 , and 6 . Condensation of 3,4-aminobenzoic acid with p-chlorobenzaldehyde in the presence of sodium metabisulphite and DMF resulted in the synthesis of benzimidazole-5-carboxylic acid ( 1 ) in a good yield [ 34 , 35 ]. Compound 1 ’s infrared spectra showed that C=O was present at 1662 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The key intermediates 1 – 3 were prepared according to previously reported procedures [ 34 , 36 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…[42] The presence of NH group in the structure of our synthesized compounds, unlike the one mentioned above, may have caused an increase in activity.In addition, as stated in the literature, the benzimidazole ring forming the basic structure in the target compounds and imine bond formation were the most important aspects determining the activity. [43,44] Unlike previous studies, the NH group at the C-2 position of the benzimidazole ring increased the activity by interacting with amino acids in the target protein (GLN282, THR276, etc. ).…”
Section: Biological Activitymentioning
confidence: 90%
“…There are many studies in the literature regarding the VEGFR‐2 inhibition of benzimidazoles (Abd El‐Lateef et al, 2023a; Abdel‐Mohsen et al, 2020a; Ali et al, 2022; Ding et al, 2020; Mostafa et al, 2019; Tong et al, 2021; Yuan et al, 2019). In 2023, a new series of Schiff base‐benzimidazole hybrids has been developed and synthesized by Abd El‐Lateef et al (2023a, 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies in the literature regarding the VEGFR‐2 inhibition of benzimidazoles (Abd El‐Lateef et al, 2023a; Abdel‐Mohsen et al, 2020a; Ali et al, 2022; Ding et al, 2020; Mostafa et al, 2019; Tong et al, 2021; Yuan et al, 2019). In 2023, a new series of Schiff base‐benzimidazole hybrids has been developed and synthesized by Abd El‐Lateef et al (2023a, 2023b). The anticancer activity of the investigated benzimidazole hybrids is associated with inhibition of the VEGFR‐2 enzyme, wherein two benzimidazoles derivatives demonstrated potent inhibition of the enzyme (86.23% and 89.89%, respectively), in comparison to Sorafenib (88.17% inhibitory activity) (Abdel‐Mohsen et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%